A tetranuclear nickel/lead complex with a salen type Schiff base: synthesis, structure and exploration of photosensitive Schottky barrier diode behaviour. (1st February 2019) - Roy, Sourav; Dey, Arka; Drew, Michael G. B.; Ray, Partha Pratim; Chattopadhyay, Shouvik
Abstract : A tetranuclear nickel(ii )/lead(ii ) complex has been synthesized and characterized. The complex based device behaves as a Schottky diode. The charge transfer kinetics of the complex is enhanced after light soaking. Abstract : An X-ray characterized tetranuclear nickel(ii )/lead(ii ) complex has been synthesized and characterized by elemental analysis, IR and single crystal X-ray diffraction studies. Single crystal X-ray analysis confirms that the complex contains two [(NiO2 )Pb] cores joined with two DMF molecules. The complex shows interesting electrical properties. The optical band gap energy of the synthesized ligand and the complex has been evaluated as 3.87 and 3.08 eV, respectively. The solid state UV measurement implies the semiconductor behavior of the complex. The complex based device has been determined experimentally to behave as a Schottky diode.